Bioacessibilidade in vitro do ácido fólico em pão francês e avaliação de sua estabilidade térmica - Neves, Daniela Andrade, 1988- (2013)
Orientadores: Helena Teixeira Godoy, Giovanna Pisanelli Rodrigues de Oliveira